Implementation assessment of perioperatory antibiotic prophylaxis guidelines in pediatric abdominal surgery. - Dagmaris Losa Pérez; Sergio Luis González López; Luis Pedro Hernández Sosa (Medisur)
Introduction: since the beginning of the 80s the term perioperative profilaxis is introduced, changing the previous criteria on antimicrobial profilaxis. This method helps to reduce the perioperative sepsis phenomenon and the medical cost, achieving more quality in pacient attention. In the surgical service area of the pediatric and universitary hospital ¨Paquito Gonzalez Cueto¨ a guide with good clinical practices in perioperative antibiotic profilaxis for abdominal surgery has been in use since the year 2000. Objective: To evaluate the following of this guide. Methods: a retrospective and descriptive study of a series of cases since february 2000 until february 2002. 235 pacients operated from abdominal affections were analized. The fallowing of the guide were tested by 4 questions, expressing the results in percentage lists. Conclussions: Despite the use of antibiotic profilaxis in more than 96% of the cases, there was a low percentage of global guide following (33,5%), since there were problems with the employed outline, dosis and moment of administration of the antibiotic, specially in surgery with high risk of developing infection of surgical injury.